Anterior femoral cut in total knee arthroplasty: a classification proposal - Medeiros, Filipe; Duarte, António; Correia, Bruno; Carvalho, Maria; Vide, João; Fontes, Ana Paula; Sousa, João Paulo (International Journal of Research in Orthopaedics, 2019)
Background: The cut of the anterior femur (CAF) sets the rotation of the femoral component, which could affect patellar tracking, and influence the clinical results on total knee arthroplasty (TKA). The aim of this study was to suggest a classification for anterior femoral cut in TKA. Methods: Images of anterior femoral cuts were aggregated in different shapes and defined a classification. One-hundred femoral image’s cuts were analysed by 5 orthopaedic surgeons, which classified them twice. To analyse inter and intra-observer agreement, the Fleiss Kappa test was used. Results: The study proposes the following CAF classification, type 1 (one peak) and type 2 (two peaks); subtypes 1 (a) a central base peak, 1 (b) a lateral base peak, 2 (a) two peaks where the smallest is in the lower half, and 2 (b) two peaks where the smallest is in the upper half. In our study, type 2 (a) was the most common type (54.5%), followed by type 1 (b). The analysis showed good intra- and inter-observer agreements (mean K of 0.774 and 0.627, respectively). The intra and inter-observer concordance was statistically significant in all the analyses. Conclusions: The CAF classification system for TKA is considered a reproducible classification. To our knowledge, there is no study describing a shape’s classification of this cut. A slight rotation of the femoral cutting guide could change the axial rotation and positioning of the femoral component. An undesirable cut could lead to different patellofemoral offset and could consequently cause anterior pain and instability.